(untitled) (Marketing Journal, 2026)
This article examines statistical methods aimed at the stable and consistent improvement of product quality in the manufacturing and installation of PVC windows and doors. Based on the application of statistical methods and diagrams, the cycle of actions i s presented in a clear and accessible manner. The use of statistical methods makes it possible to develop optimal management decisions based on factual data and ensures continuous improvement of technological production processes. № 1 -SON YANVA R, 202 6-YIL 530